Impact of pump electrification on crop diversification in Bangladesh: Evidence from the Bangladesh integrated household survey - Banerjee, Anurag; Chakraborty, Shreya; Deepak Varshney (Elsevier, 2024)
Bangladesh's agricultural sector, crucial to its economy, has undergone a significant transformation in recent years, largely due to the shift from diesel to electric irrigation pumps. This study investigates the impact of this energy transition on crop diversification. While there is extensive literature on crop diversification, the effects of changing energy sources have remained underexplored. Leveraging the substantial increase in pump electrification over the past decade, we utilize data from the Bangladesh Integrated Household Survey (BIHS) for 2011, 2015, and 2018 to examine this shift. Our hypothesis posits that the transition to electric pumps influences cropping patterns by lowering irrigation costs. Using difference-indifferences (DID) and fixed effect model, we find that pump electrification significantly alters cropping patterns. Specifically, we observe a 5.5 percentage point increase in paddy cultivation and a 4.9 percentage point decrease in non-paddy crops. Notably, the rise in the overall paddy proportion is primarily driven by an increase in boro paddy cultivation, while the decline in non-paddy crops is attributed to a reduction in wheat cultivation. These findings highlight the effects of cheaper irrigation through electric pumps, which may disproportionately favor waterintensive paddy cultivation. Policymakers should consider these insights when designing strategies to promote more diverse and nutritionally beneficial cropping patterns.